2010
DOI: 10.1007/s00449-010-0451-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of submerged culture conditions on exopolysaccharides production by Armillaria luteo-virens Sacc QH and kinetic modeling

Abstract: This work aimed to develop the submerged cultivation conditions for improved exopolysaccharides (EPS) production by Armillaria luteo-virens Sacc. The effects of culture temperature, aeration rate, inoculum level, initial pH, and additives on EPS formation and mycelial growth are investigated. The aeration rate, initial pH, and inoculum level significantly affected EPS production under the submerged cultivation. The developed conditions were as follows: cultivation temperature 23 °C, initial pH 5.0, aeration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…Higher aeration rates seem to reduce the EPS production. Xu et al reported that the optimal condition for EPS production of Armillaria luteo‐virens Sacc QH by submerged cultures was at a low aeration rate of 0.5 vvm 21, which is equivalent to that from our results. It is possible that higher aeration rates provide suitable environments for metabolic pattern of cell growth but not for EPS biosynthesis, resulting in an inhibition in EPS formation at a slightly high DO concentration.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Higher aeration rates seem to reduce the EPS production. Xu et al reported that the optimal condition for EPS production of Armillaria luteo‐virens Sacc QH by submerged cultures was at a low aeration rate of 0.5 vvm 21, which is equivalent to that from our results. It is possible that higher aeration rates provide suitable environments for metabolic pattern of cell growth but not for EPS biosynthesis, resulting in an inhibition in EPS formation at a slightly high DO concentration.…”
Section: Resultssupporting
confidence: 83%
“…Submerged culture is an efficient polysaccharide production approach by mushrooms 11–13, 20. Considerable attention has been focused in the last decade on polysaccharide production optimization of submerged cultures from a variety of edible and medicinal mushrooms 16, 20, 21. Several reports pointed out that yield, chemical structure, molecular weight and biological properties of fermented polysaccharides in submerged cultures depend highly on environmental conditions and nutritional compositions 13, 20–23.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, A. luteo-virens has been traditionally consumed by local residents because of its excellent flavor and texture (Li, 2005). Recently, more attentions have been paid to this wild mushroom including isolation of lectin (Feng et al, 2006) and polysaccharides (Liu, Yu, Mao, Meng, & Liu, 2007), cultivation of mycelium (Jiao, Chen, Zhou, Zhang, & Chen, 2008;Xu, Fu, Chen, & Liu, 2010) and investigation of antioxidative and antitumor activities (Li, Chen, & Bi, 2004). Furthermore, eighteen amino acids, three vitamins (Diao, 1997) and ten minerals (Li & Diao, 2008) have been found in A. luteo-virens.…”
Section: Introductionmentioning
confidence: 99%